The Christian myth : origins, logic, and legacy - Mack, Burton L (New York : Continuum, 2001)
"It is now nearly a century since the book known in English as The Quest of the Historical Jesus initiated successive waves of reassessment of the figure who is arguable by the most influential in two millennia of Western civilization. Beyond the traditional religious view of Jesus as son of God and savior, recent decades have seen him depicted as peasant teacher, revolutionary leader, mystic and visionary, miracle-working prophet. The Christian Myth rejects these various portrayals as being not only based on a priori assumptions about Jesus and therefore contradictory of one another, but also as untrue to the many images of Jesus produced by the early Christians. In short, "the quest" has proven to be a failure." "This failure stems in large part from taking the canonical gospels as history, and ignoring the pre-gospel and extra-gospel accounts from the earliest layers of Jesus stories and sayings. Those layers disclose a widespread and variegated mythmaking process in the earliest schools and communities of Jesus' followers that was generated by social, economic, even geographical "interests." What is needed, Burton Mack suggests, is a systematic analysis of those interests which is not driven by either personal ("meeting Jesus") or theological ("building Church") motives, but which seeks to redescribe and understand the cultural and anthropological modalities whereby Christian myths and rituals were first conceived and agreed upon."--Jacket
The Historical Jesus hoopla -- The Case for a cynic-like Jesus -- On Redescribing Christian origins -- Explaining Religion: a theory of social interests -- Explaining Christian mythmaking: a theory of social logic -- Innocence, power, and purity in the Christian imagination -- Christ and the creation of a monocratic culture -- The Christian myth and the Christian nation
Includes bibliographical references (p/ 223-237)
Keywords: Christianity -- Origin; Christianity and culture